Inhibition of cholesterol transport in an intestine cell model by pine-derived phytosterols. (October 2016) - Yi, Jinsoo; Knudsen, Tine A.; Nielsen, Anne-Louise; Duelund, Lars; Christensen, Morten; Hervella, Pablo; Needham, David; Mouritsen, Ole G.
Graphical abstract: A commercial pine-derived phytosterol formulation as well as β-sitosterol inhibit cholesterol transport in an intestine cell model system Highlights: Pine-derived phytosterols as well as β-sitosterol was found to inhibit cholesterol transport in an HT-29 MTX intestinal cell model. The artificial intestinal fluid used was composed of digested fats with sterols, mimicking the conditions for fat digestion in the intestine. Six potential oral supplements of the pine-derived phytosterols were tested in the mimicking condition of acidic stomach and neutral intestine. Four of the formulations demonstrated effective inhibition of cholesterol transport. Abstract: We have quantified the inhibition of intestinal cholesterol transport by pine-derived phytosterols using an HT29-MTX intestine cell model that forms a mucus layer similar to that in the intestine. An artificial intestinal fluid consisting of digested fat, bile salt, cholesterol, and phytosterols was formulated in order to mimic the conditions in the intestine. The apparent permeability coefficient ( P app ) of the positive control, i.e., 0.1 mM of cholesterol solubilized in the artificial intestine fluid, was found to be 0.33 (± 0.17) × 10 −6 cm/s. When 0.1 mM β-sitosterol was solubilized alongside, P app was effectively zero, corresponding to a total inhibition of cholesterol transport. A similar strong inhibition was found when commercial pine-derived phytosterols, PinVita™ FSP DuPont, were co-solubilized with cholesterol in the dietary model micelles, leading to P app = 0.06 (± 0.06) × 10 −6 cm/s, i.e., 5.5 times lower than the cholesterol positive control. Additionally, the effect of potential oral administration formulations generated by the pine-derived phytosterols was also characterized. The formulations were produced as a liquid formulation of the cholesterol-containing artificial intestine fluid. Six liquid formulations were tested of which four displayed a P app in the range of 0–0.09 × 10 −6 cm/s. The remaining two formulations did not show any inhibition effect on cholesterol transport and even enhanced cholesterol transport. It was furthermore observed that the phytosterols were found in the collected intestine cells but not transported to the basolateral region in the intestinal cell model system.